Self-sustaining type shale gas flowback fluid in-situ remediation method and self-sustaining type shale gas flowback fluid in-situ remediation system
By combining Ag-g-C3N4/TiO2/Ti cathode electrode and carbon-encapsulated wire mesh anode electrode, the coupling technology between photoelectro-catalysis and microbial fuel cell is used to solve the problem of low cathode utilization efficiency of sediment microbial fuel cell, and efficient shale gas reflux liquid purification and energy recovery are achieved.
Patent Information
- Application Number
- CN202411984226.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-31
AI Technical Summary
When existing sediment microbial fuel cells treat shale gas reflux, the cathode utilization efficiency is not high, resulting in low water purification efficiency and high cost and difficult to sustain effect.
The Ag-g-C3N4/TiO2/Ti cathode electrode is combined with the carbon-encapsulated wire mesh anode electrode, and the photosynthesis biological algae and indigenous microorganisms are used for collaborative purification through photoelectro-catalysis and photosynthesis of photosynthetic biological algae and indigenous microorganisms.
It improves the utilization rate of the cathode, promotes the diffusion rate of pollutants in the sediment, enhances the purification performance of water bodies, is low in cost and easy to manage, and realizes efficient purification of sewage and energy recovery.
Smart Images

Figure HDA0005222196300000011 
Figure HDA0005222196300000012 
Figure HDA0005222196300000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sewage resource utilization and environmental protection, and in particular to a method and system for in-situ repair of self-sustaining shale gas flowback fluid. Background Art
[0002] As an important unconventional natural gas resource, shale gas is being exploited around the world. Hydraulic fracturing is a key technology for shale gas exploitation. During the fracturing process, a large amount of fracturing fluid is injected into the deep underground layer. After the fracturing operation is completed, part of the mixture of fracturing fluid and formation water gradually flows back from the formation to the surface under the action of pressure difference to form flowback fluid. The flowback process usually takes place within a few days to a few weeks after fracturing, but the production of flowback fluid may last for a long time. The flowback fluid contains fracturing fluid components, formation water, and some new substances that may be produced. At the same time, the nature of formation water is relatively complex, containing a variety of inorganic salt ions, and may also contain some naturally occurring hydrocarbon compounds, organic acids and other organic substances. Therefore, the flowback fluid has the characteristics of complex composition, high salt, and high organic content. Improper treatment will cause serious pollution to the environment such as groundwater and soil. At the same time, with increasingly stringent environmental protection regulations, the efficient treatment of shale gas development flowback fluid has become a key issue.
[0003] At present, the treatment of shale gas flowback fluid mainly uses a combination of physical and chemical treatment technologies such as filtration, flotation, centrifugal separation, coagulation and sedimentation, oxidation treatment, acid-base neutralization, and their combined technologies. However, these technologies involve multiple links such as equipment investment, reagent consumption, energy consumption, and subsequent sludge treatment, which leads to complex processes, difficult operation and maintenance, and high treatment costs, limiting their promotion and application. The use of microbial methods to treat shale gas flowback fluid has unique advantages. Degrading organic pollutants in the flowback fluid into harmless substances is one of the current research hotspots. However, the microbial method also faces many challenges, such as the high salinity and complex components of the flowback fluid may inhibit microbial activity. Therefore, it is necessary to further strengthen technological research and development and innovation to develop efficient, economical, and environmentally friendly treatment technologies for shale gas flowback fluid.
[0004] Sediment microbial fuel cells use indigenous microorganisms in the sediment to directly degrade organic pollutants and also achieve energy recovery. They have great application prospects in pollutant control and environmental remediation. However, there are still many problems that need to be solved with this technology. First, its efficiency is still relatively low and the cycle is too long. Secondly, the overlying water body also contains a large amount of pollutants. At the same time, the pollutants in the sediment will continue to be released to the overlying water, aggravating the deterioration of the water quality of the overlying water body. Thirdly, the low dissolved oxygen in the overlying water has become one of the technical difficulties restricting its large-scale application. Mechanical aeration has problems such as high cost and difficulty in maintaining the effect. In addition, the cathode is generally used for oxygen reduction reaction, and the utilization efficiency of the cathode is not high.
[0005] In view of this, the present invention provides a method and system for in-situ repair of self-sustaining shale gas flowback fluid, which not only effectively makes up for the deficiencies of the prior art. Summary of the invention
[0006] The present invention aims to provide a self-sustaining method and system for in-situ repair of shale gas flowback fluid, so as to solve the technical problem of low cathode utilization efficiency when treating flowback fluid in existing sediment microbial fuel cells.
[0007] To achieve the above object, the present invention adopts the following technical solution: a method for in-situ repair of self-sustaining shale gas flowback fluid, comprising the following steps:
[0008] Step 1: Preparation of Ag-g-C3N4 / TiO2 / Ti cathode electrode
[0009] S1-1: Prepare solution: disperse hexadecyltrimethylammonium chloride and sodium hydroxide in water to obtain a mixed solution A; disperse silver nitrate and dicyandiamide in water to obtain a mixed solution B;
[0010] S1-2: Preparation of cathode electrode material: firstly, the titanium mesh is placed in the mixed solution A for hydrothermal reaction, and after cooling, it is immersed in a hydrochloric acid solution and washed with deionized water; then, it is calcined, cooled, and immersed in the mixed solution B, and freeze-dried; finally, it is wrapped with tin foil and calcined to obtain Ag-g-C3N4 / TiO2 / Ti cathode electrode material;
[0011] S1-3: Preparation of cathode electrode: placing activated carbon fiber felt and Ag-g-C3N4 / TiO2 / Ti cathode electrode material in parallel, surrounding the edges with polyethylene plastic foam to form an internal cavity, and filling the cavity with photosynthetic algae to obtain a cathode electrode;
[0012] Step 2: Preparation of carbon-wrapped wire mesh anode electrode
[0013] S2-1, pre-treatment of wire mesh;
[0014] S2-2, preparing a ligand solution: dispersing o-phenanthroline and terephthalic acid in water, adjusting the pH, and obtaining a ligand solution;
[0015] S2-3, preparing the anode electrode: subjecting the pretreated wire mesh sample to a hydrothermal reaction in the ligand solution, taking out the wire mesh, rinsing it, and then calcining it under a protective gas, and cooling it to obtain the anode electrode;
[0016] Step 3: System construction and operation
[0017] S3-1. Installation system: In a waste liquid system to be treated having a bottom mud layer and a water layer after standing, the above-mentioned anode electrode is installed in the bottom mud layer, and the cathode electrode is installed in the water layer. When the cathode electrode is installed, one side of the Ag-g-C3N4 / TiO2 / Ti electrode faces upward, and one side of the activated carbon fiber felt faces downward;
[0018] S3-2. System operation: The anode electrode and the cathode electrode are connected to each other through a wire and connected to a battery; samples are collected from the overlying water and bottom sediment regularly to determine the restoration efficiency of the water body and bottom sediment.
[0019] The principle of this scheme is:
[0020] This scheme uses clean and cheap sunlight and indigenous microorganisms in the sediment as driving forces, adds photosynthetic algae into the internal cavity formed by the Ag-g-C3N4 / TiO2 / Ti electrode and carbon felt, and suspends them in the overlying water as the cathode electrode; a carbon-wrapped wire mesh is prepared by hydrothermal combined with high-temperature carbonization method and buried flat in the sediment as the anode electrode; the anode electrode and the cathode electrode are connected by wires and connected to a battery to collect electrical energy. This system couples photoelectrocatalysis with sedimentation-type microbial fuel cells, giving full play to the advantages of both and avoiding their disadvantages, thereby achieving the purpose of coordinated purification of overlying water and sediment. In addition, this scheme not only achieves the purification of sewage return liquid, but also collects electrical energy, effectively realizing the resource utilization of sewage and improving environmental protection benefits.
[0021] The advantages of this solution are:
[0022] 1. Compared with the low efficiency of cathode utilization in the prior art, this solution realizes the simultaneous degradation of pollutants by the cathode and anode, which not only improves the utilization rate of the cathode, but also promotes the diffusion rate of pollutants in the sediment, improves the performance of water purification, and is low in cost and easy to control and manage.
[0023] 2. This scheme couples photoelectrocatalysis with sedimentation-type microbial fuel cells, which can transfer the electrons generated by the anode of the sedimentation-type microbial fuel cell to the cathode, promote the metabolism of microorganisms, enhance the sediment remediation performance, and overcome the shortcomings of cathode photoelectrocatalytic materials such as easy recombination of photogenerated charges and low catalytic efficiency, improve the degradation performance of overlying water pollutants, give full play to the advantages of both and avoid their shortcomings, so as to achieve the purpose of coordinated purification of overlying water and sediment.
[0024] 3. This scheme uses carbon felt as a fixed bed for photosynthetic algae, and utilizes the characteristics of photosynthetic oxygen production of algae to improve the reaction efficiency of oxygen and cathode photoelectrode, producing more hydroxyl free radicals (·OH), peroxyl free radicals (·O2 -) and hydrogen peroxide (H2O2), which promotes the purification rate of overlying water and solves the technical problems that restrict the large-scale application of microbial fuel cells.
[0025] 4. The Ag-g-C3N4 / TiO2 / Ti cathode electrode material developed in this scheme has antibacterial properties and can effectively inhibit the growth of microorganisms on the surface of the cathode electrode, making maximum use of clean and cheap sunlight, ensuring the overlying water restoration performance and long-term operation stability.
[0026] 5. This solution is driven by clean and cheap sunlight and indigenous microorganisms in the sediment. It is a green and environmentally friendly remediation technology. In addition, it has the advantages of simple electrode production, good stability, long service life, simple system structure, no need for additional maintenance, and small investment. It can achieve self-sustaining, durable, and large-scale in-situ remediation of shale gas return fluid, black and smelly lake water, and other polluted water bodies, and has a broad application space.
[0027] Preferably, as an improvement, in S1-1, the mass ratio of hexadecyltrimethylammonium chloride, sodium hydroxide and water in the mixed solution A is 16-64:240:1000; the mass ratio of dicyandiamide, silver nitrate and water in the mixed solution B is 16.81-37.62 g:0.1699-0.8494:100.
[0028] Beneficial effect: This scheme adopts the above-mentioned setting, which is convenient for producing Ag-g-C3N4 / TiO2 / Ti cathode electrode materials with excellent performance. The applicant has found through long-term experiments that if the amount of hexadecyltrimethylammonium chloride in the mixed solution A is too little, the TiO2 crystal nucleus will easily grow excessively, forming larger particles with a smaller specific surface area, which is not conducive to the immobilization of Ag-g-C3N4; if the amount of hexadecyltrimethylammonium chloride is too much, the shape of the crystal will be irregular due to the change in the growth direction of the crystal; if the amount of sodium hydroxide in the mixed solution A is too little, the TiO2 will not be able to completely cover the surface of the titanium sheet due to insufficient alkalinity; if the amount of sodium hydroxide is too much, it will cause TiO2 to fall off easily. If the amount of dicyandiamide in the mixed solution B is too small, the g-C3N4 content will be low due to the small amount of carbon precursor; if the amount of dicyandiamide is too large, the g-C3N4 covering layer will be thicker due to the excessive carbon precursor, reducing the effective electron transfer; if the amount of silver nitrate in the mixed solution B is too small, the Ag component will be too small; if the amount of silver nitrate is too much, the Ag particle size will be larger and the dispersion will be poor.
[0029] Preferably, as an improvement, in S1-2, the hydrothermal reaction is a hydrothermal reaction at 140-160°C for 24 hours; the immersion in the hydrochloric acid solution is an immersion in a 1-2M hydrochloric acid solution for 24 hours; the calcination is heating to 500-550°C at a rate of 2-4°C / min and keeping warm for 2.5-4 hours.
[0030] Beneficial effect: This scheme adopts the above-mentioned setting, which is convenient for producing Ag-g-C3N4 / TiO2 / Ti cathode electrode materials with excellent performance. The applicant has found through long-term experiments that if the hydrothermal reaction temperature is too high, the TiO2 crystal nucleus growth rate will be fast, and larger particles will be easily formed, resulting in a smaller contact interface with Ag-g-C3N4; if the hydrothermal reaction temperature is too low, it will be difficult to form TiO2 crystal nuclei due to insufficient corrosion. If hydrochloric acid impregnation is not used after the hydrothermal reaction, its sodium ions will adhere to its surface; if the hydrochloric acid impregnation concentration after the hydrothermal reaction is too high, the TiO2 crystal nucleus will be easy to detach; if the hydrochloric acid impregnation concentration after the hydrothermal reaction is too low, TiO2 will not be effectively formed. If the calcination temperature after hydrochloric acid impregnation is too high or the temperature rises too quickly, the TiO2 flakes will easily detach; if the calcination temperature after hydrochloric acid impregnation is too low or the temperature rises too slowly, the TiO2 crystal nucleus will not grow completely, affecting its crystal structure; if the calcination time after hydrochloric acid impregnation is too long, the TiO2 crystal nucleus will easily detach; if the calcination time after hydrochloric acid impregnation is too short, the TiO2 crystal nucleus will not grow completely, affecting its crystal structure.
[0031] Preferably, as an improvement, in S1-2, the immersion time in the mixed solution B is 24 to 36 hours; and the calcination is performed at 520 to 540° C. for 4 hours.
[0032] Beneficial effect: This scheme adopts the above-mentioned setting, which is convenient for producing Ag-g-C3N4 / TiO2 / Ti cathode electrode materials with excellent performance. The applicant found through long-term experiments that if the immersion time of mixed solution B is too short, the Ag particles will be larger and easy to agglomerate due to incomplete ion exchange, affecting the performance of the electrode; if the immersion time of mixed solution B is too long, the TiO2 crystal nucleus will be easy to detach due to excessive ion exchange reaction, affecting the long-term stability of the electrode. If the calcination temperature is too high, too little g-C3N4 will be formed due to excessive pyrolysis of the carbon precursor; if the calcination temperature is too low, the material will have a poor crystal form and poor catalytic performance due to incomplete pyrolysis of the carbon precursor; if the calcination time is too long, the Ag particles will have a larger particle size due to excessive growth of the Ag crystal nucleus; if the calcination time is too short, the material will have a poor crystal form and poor catalytic performance due to incomplete pyrolysis of the carbon precursor.
[0033] Preferably, as an improvement, in S1-3, the distance between the activated carbon fiber felt and the Ag-g-C3N4 / TiO2 / Ti cathode electrode is 2 to 3 cm.
[0034] Beneficial effects: This scheme adopts the above-mentioned setting, which is convenient for producing Ag-g-C3N4 / TiO2 / Ti cathode electrodes with excellent performance. The applicant has found through long-term experiments that if the spacing is too long, the oxygen generated will not be able to fully contact the cathode electrode due to oxygen diffusion, reducing the effective utilization of the generated oxygen; if the spacing is too short, the photosynthetic algae will directly contact the cathode electrode, resulting in the biological activity of the photosynthetic algae and the cathode electrode's utilization efficiency of sunlight being reduced.
[0035] Preferably, as an improvement, in S2-1, the pretreatment of the wire mesh includes immersing the wire mesh in 0.5M hydrochloric acid solution, 1M sodium hydroxide solution and water for 2 hours in sequence; then placing the wire mesh in a muffle furnace and heat treating it at 300-350°C for 2 hours to obtain a pretreated wire mesh sample.
[0036] Beneficial effect: This scheme adopts the above-mentioned setting, which is convenient for pre-treating the wire mesh and improving the performance of the prepared anode electrode. The applicant has found through long-term experiments that if the baking temperature in the muffle furnace after impregnation is too low, the subsequent carbon wrapping will be uneven due to the unclean surface of the wire mesh, affecting the long-term stability of the electrode; if the baking temperature in the muffle furnace after impregnation is too high, the wire mesh will be deformed, making its pore size and surface properties difficult to control.
[0037] Preferably, as an improvement, in S2-2, the mass ratio of o-phenanthroline, terephthalic acid and water in the ligand solution is 0.18-0.36:0.66:50.
[0038] Beneficial effect: This scheme adopts the above-mentioned setting, which is convenient for preparing an anode electrode with excellent performance. The applicant has found through long-term experiments that if the amount of o-phenanthroline in the ligand solution is too little, the subsequent carbon wrapping will be uneven due to the overflow of iron elements; if the amount of o-phenanthroline is too much, the carbon layer will be thick, resulting in a low degree of graphitization; if the amount of terephthalic acid in the ligand solution is too little, the subsequent carbon wrapping will be uneven due to the inability to occur an effective coordination reaction; if the amount of terephthalic acid is too much, the terephthalic acid loss will be serious, resulting in a high cost.
[0039] Preferably, as an improvement, in S2-3, the hydrothermal reaction is carried out at 120-140°C for 24-48h, the wire mesh is taken out, rinsed clean, and placed in a muffle furnace, with argon or nitrogen as a protective gas, and the temperature is increased to 850-900°C at a rate of 3-5°C / min, kept warm for 2-3h, and cooled to room temperature to obtain the anode electrode material.
[0040] Beneficial effect: This scheme adopts the above-mentioned setting, which is convenient for preparing an anode electrode with excellent performance. The applicant has found through long-term experiments that if the hydrothermal reaction temperature is too high, the carbon coating will be uneven due to the rapid growth rate of the crystal nucleus, affecting the long-term stability of the electrode; if the hydrothermal reaction temperature is too low, it will be difficult to form a carbon material due to the inability to stimulate the coordination reaction; if the hydrothermal reaction time is too short, the coordination reaction will be incomplete, resulting in uneven carbon coating, affecting the long-term stability of the electrode; if the hydrothermal reaction time is too long, the carbon layer will be easy to detach. If no protective gas is used during the calcination in the muffle furnace after the hydrothermal reaction, the carbon precursor will undergo a combustion reaction and the carbon material will not be formed; if the calcination temperature is too high or the temperature rises too quickly after the hydrothermal reaction, the graphitization of the carbon material will not be high and the wrapping will be poor; if the calcination temperature is too low or the temperature rises too slowly, the crystal form of the carbon material will not be high, increasing the production cost; if the calcination and insulation time in the muffle furnace is too long, it will result in a large loss of carbon material and increased energy consumption; if the calcination and insulation time is too short, the graphitization of the carbon material will not be high due to insufficient nucleus growth.
[0041] Preferably, as an improvement, the present scheme also provides an Ag-g-C3N4 / TiO2 / Ti cathode electrode material, and the Ag-g-C3N4 / TiO2 / Ti cathode electrode material is prepared by the above method.
[0042] Preferably, as an improvement, the present scheme also provides a self-sustaining system for in-situ remediation of shale gas flowback fluid, comprising a waste liquid system to be treated having a mud layer and a water layer after standing, a cathode electrode being provided in the water layer, an anode electrode being provided in the mud layer, and the anode electrode being 2 to 10 cm away from the contact interface between the water layer and the mud layer; the anode electrode is the carbon-wrapped wire mesh prepared as described above; the cathode electrode is the Ag-g-C3N4 / TiO2 / Ti cathode electrode prepared as described above, and when the cathode electrode is installed, the Ag-g-C3N4 / TiO2 / Ti cathode electrode material side faces upward, the activated carbon fiber felt side faces downward, and the cathode electrode is horizontally suspended 2 to 10 cm below the water surface; the anode electrode is connected to the cathode electrode by a wire and is connected to a battery for collecting electrical energy. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 Schematic diagram of the structure of the Ag-g-C3N4 / TiO2 / Ti cathode electrode in an embodiment of the present invention.
[0044] Figure 2 It is a schematic structural diagram of a self-sustaining shale gas flowback fluid in-situ repair system in an embodiment of the present invention.
[0045] Figure 3 The removal rate curve of organic matter in sediment under different experimental conditions
[0046] Figure 4 TOC removal rate curve of overlying water under different experimental conditions
[0047] Figure 5 The ammonia nitrogen removal rate curve of overlying water under different experimental conditions
[0048] Figure 6 It is a curve diagram of ammonia nitrogen removal rate of overlying water under the operating conditions of Example 1, Example 2, Comparative Example 1, Comparative Example 4 and Comparative Example 5. DETAILED DESCRIPTION
[0049] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto. Unless otherwise specified, the technical means used in the following examples and experimental examples are conventional means well known to those skilled in the art, and the materials, reagents, etc. used can be obtained from commercial sources.
[0050] The figure marks in the drawings of the specification include: Ag-g-C3N4 / TiO2 / Ti cathode electrode material 1, cavity 2, polyethylene plastic foam 3, photosynthetic algae 4, activated carbon fiber felt 5, cathode electrode 6, water layer 7, water surface 8, wire 9, battery 10, interface 11, anode electrode 12, bottom mud layer 13, sunlight 14.
[0051] Program Overview
[0052] This solution provides a self-sustaining shale gas flowback fluid in-situ repair method, comprising the following steps:
[0053] Step 1, a method for preparing Ag-g-C3N4 / TiO2 / Ti cathode electrode material, the steps are as follows:
[0054] S1-1: Prepare solution: dissolve hexadecyltrimethylammonium chloride (CTAC) and NaOH in H2O, control the mass ratio of CTAC:NaOH:H2O to be (16-64):240:1000, and obtain a uniform mixed solution A; weigh 16.81-37.62 g of dicyandiamide and 0.1699-0.8494 g of AgNO3, add silver nitrate and dicyandiamide to 100 ml of H2O, stir, and obtain a mixed solution B.
[0055] S1-2: Preparation of cathode electrode material: Transfer the mixed solution A to a polytetrafluoroethylene reactor, control the filling amount to 60-80%, then place the titanium mesh vertically in the middle of the reactor, and hydrothermally react at 140-160°C for 24 hours. After cooling to room temperature, immerse it in a 1-2M HCl solution for 24 hours and wash it with deionized water. Then, place it in a muffle furnace, heat it to 500-550°C at a rate of 2-4°C / min, keep it warm for 2.5-4 hours, cool it to room temperature, immerse the obtained sample in the mixed solution B for 24-36 hours, and then freeze-dry it. Then, wrap it with tin foil and calcine it at 520-540°C for 4 hours. By adjusting the composition of the mixed solution B, Ag-g-C3N4 / TiO2 / Ti cathode electrode materials of different components are obtained.
[0056] This solution also provides an Ag-g-C3N4 / TiO2 / Ti cathode electrode material, which is prepared by the above method.
[0057] S1-3: Preparation of cathode electrode: placing activated carbon fiber felt and Ag-g-C3N4 / TiO2 / Ti cathode electrode in parallel, surrounding the edge with polyethylene plastic foam to form an internal cavity, and filling the cavity with photosynthetic algae to obtain a cathode electrode;
[0058] Specifically, this solution also provides a Ag-g-C3N4 / TiO2 / Ti cathode electrode, such as Figure 1 As shown, it includes activated carbon fiber felt 5 and Ag-g-C3N4 / TiO2 / Ti cathode electrode material 1 (prepared by the method in the above step one) placed in parallel, with a spacing of 2 to 3 cm to form a sandwich, and polyethylene plastic foam 3 is laid around the sandwich to form an internal cavity 2, and the cavity 2 is filled with photosynthetic algae 4.
[0059] The present solution also provides a method for installing an Ag-g-C3N4 / TiO2 / Ti cathode electrode, comprising the following contents: when installing the cathode electrode, the Ag-g-C3N4 / TiO2 / Ti cathode electrode material 1 is facing upward and the activated carbon fiber felt 5 is facing downward. By adjusting the width and thickness of the polyethylene plastic foam 3, the cathode electrode is horizontally suspended at different depths below the water surface 8.
[0060] As a reference, when treating the flowback liquid in this scheme, the cathode electrode is horizontally suspended 2 to 10 cm below the water surface by adjusting the width and thickness of the interlayer polyethylene plastic foam to form a cathode electrode.
[0061] Step 2, a method for preparing a carbon-wrapped wire mesh anode electrode, the steps are as follows:
[0062] S2-1. Pretreatment of wire mesh: Soak the wire mesh in 0.5M HCl, 1M NaOH, and H2O for 2 hours in sequence. Place the wire mesh in a muffle furnace and heat treat it at 300-350°C for 2 hours to obtain a pretreated wire mesh sample.
[0063] S2-2. Prepare ligand solution: Take o-phenanthroline and terephthalic acid as ligands, dissolve them in 50 mL H2O, add 0.5 mol / L HNO3 dropwise, adjust the pH to 5, control the mass ratio of o-phenanthroline: terephthalic acid: H2O to (0.18-0.36): 0.66:50, and obtain a ligand solution.
[0064] S2-3. Preparation of anode electrode: transfer the ligand solution to a hydrothermal reactor and control the filling amount to 60-80%. Then, place the pretreated wire mesh sample into the reactor and perform a hydrothermal reaction at 120-140°C for 24-48 hours. Take out the wire mesh, rinse it, and place it in a muffle furnace. Use argon or nitrogen as a protective gas and heat it to 850-900°C at a rate of 3-5°C / min. Keep it warm for 2-3 hours and cool it to room temperature to obtain the anode electrode material.
[0065] The present invention also provides a carbon-wrapped wire mesh anode electrode, which is prepared by the above method.
[0066] Step 3: System construction and operation
[0067] S3-1. Installation system: This solution also provides a self-sustaining shale gas flowback fluid in-situ repair system, such as Figure 2 As shown, it includes a waste liquid system to be treated having a sludge layer 13 and a water layer 7 after standing, a cathode electrode 6 is provided in the water layer 7, an anode electrode 12 is provided in the sludge layer 13, and the anode electrode 12 is 2 to 10 cm away from the interface 11 where the water layer 7 and the sludge layer 13 contact.
[0068] As a reference, the anode electrode 12 in this scheme is a carbon-wrapped wire mesh (prepared by the method in step 2 above). The cathode electrode 6 includes an activated carbon fiber felt 5 and an Ag-g-C3N4 / TiO2 / Ti cathode electrode material (prepared by the method in step 1 above) placed in parallel, with a spacing of 2 to 3 cm to form an interlayer, and polyethylene plastic foam 3 is laid around the interlayer to form an internal cavity 2, and the cavity 2 is filled with photosynthetic algae 4. When the cathode electrode 6 is installed, the Ag-g-C3N4 / TiO2 / Ti cathode electrode material faces up and the activated carbon fiber felt 5 faces down. In this scheme, by adjusting the width and thickness of the interlayer polyethylene plastic foam 3, the cathode is horizontally suspended 2 to 10 cm below the water surface 8 to form a cathode electrode 6.
[0069] S3-2, system operation: the anode electrode 12 is connected to the cathode electrode 6 through the wire 9, and is connected to the battery 10 for collecting electrical energy. At this point, it is considered that the system has been successfully started, and samples can be collected from the overlying water and bottom mud regularly to determine the restoration efficiency of the water body and bottom mud.
[0070] Example 1
[0071] Step 1: Preparation of Ag-g-C3N4 / TiO2 / Ti cathode electrode
[0072] 1.6g hexadecyltrimethylammonium chloride (CTAC) and 24g NaOH were dissolved in 100ml H2O to obtain a uniform mixed solution A; 16.81g dicyandiamide and 0.1699g AgNO3 were added to 100ml H2O and stirred to obtain a mixed solution B. The mixed solution A was transferred to a polytetrafluoroethylene reactor, and the filling amount was controlled to be 60%. Then, a 5cm*5cm titanium mesh was placed vertically in the middle of the reactor and hydrothermally reacted at 160℃ for 24h. After cooling to room temperature, it was immersed in a 1M HCl solution for 24h and washed with deionized water. Then, it was placed in a muffle furnace, heated to 500℃ at a rate of 3℃ / min, kept warm for 2.5h, cooled to room temperature, and the obtained sample was immersed in mixed solution B for 24h, and then freeze-dried. Then, after wrapping with tin foil, it was calcined at 520°C for 4 h to obtain the Ag-g-C3N4 / TiO2 / Ti cathode electrode material.
[0073] The prepared Ag-g-C3N4 / TiO2 / Ti electrode was placed in parallel with a 5cm*5cm carbon felt with a spacing of 3cm. Polyethylene plastic foam with a width of 0.5cm was laid around the interlayer to form an internal cavity. Photosynthetic algae were added into the internal cavity to obtain a cathode electrode.
[0074] Step 2: Preparation of carbon-wrapped wire mesh anode electrode
[0075] Soak a 5cm*5cm wire mesh in 0.5M HCl, 1M NaOH, and H2O for 2h in turn. Place the wire mesh in a muffle furnace and heat treat it at 300℃ for 2h to obtain a pretreated wire mesh sample. Dissolve 0.3412g of o-phenanthroline and 0.66g of terephthalic acid in 50mL H2O, add 0.5mol / L of HNO3 dropwise, adjust the pH to 5, and obtain a ligand solution. Transfer the ligand solution to a hydrothermal reactor, control the filling amount to 80%, then place the wire mesh sample in the reactor, hydrothermally react at 120℃ for 24h, take out the wire mesh, rinse it, and place it in a muffle furnace. Use argon or nitrogen as a protective gas, heat it to 900℃ at a rate of 5℃ / min, keep it warm for 2h, and cool it to room temperature to obtain an anode electrode.
[0076] Step 3: System construction and operation
[0077] The prepared carbon-wrapped wire mesh was buried flat at 5 cm below the interface between the bottom mud and water to form an anode electrode; the Ag-g-C3N4 / TiO2 / Ti surface of the prepared cathode electrode was facing upward and the activated carbon fiber felt surface was facing downward, the width of the interlayer polyethylene plastic foam was adjusted, and the cathode was horizontally suspended 2 cm below the water surface to form a cathode electrode; the anode electrode and the cathode electrode were connected to the battery through a wire, and the system was successfully started.
[0078] Example 2
[0079] Step 1: Preparation of Ag-g-C3N4 / TiO2 / Ti cathode electrode
[0080] 3.2g hexadecyltrimethylammonium chloride (CTAC) and 24g NaOH were dissolved in 100ml H2O to obtain a uniform mixed solution A; 36.62g dicyandiamide and 0.4696g AgNO3 were added to 100ml H2O and stirred to obtain a mixed solution B. The mixed solution A was transferred to a polytetrafluoroethylene reactor, and the filling amount was controlled to be 60%. Then, a 5cm*5cm titanium mesh was placed vertically in the middle of the reactor and hydrothermally reacted at 160℃ for 24h. After cooling to room temperature, it was immersed in a 1M HCl solution for 24h and washed with deionized water. Then, it was placed in a muffle furnace, heated to 500℃ at a rate of 3℃ / min, kept warm for 4h, cooled to room temperature, and the obtained sample was immersed in mixed solution B for 24h, and then freeze-dried. Then, after wrapping with tin foil, it was calcined at 520°C for 4 h to obtain the Ag-g-C3N4 / TiO2 / Ti cathode electrode material.
[0081] The prepared Ag-g-C3N4 / TiO2 / Ti electrode was placed in parallel with a 5cm*5cm carbon felt with a spacing of 3cm. Polyethylene plastic foam with a width of 0.5cm was laid around the interlayer to form an internal cavity. Photosynthetic algae were added into the internal cavity to obtain a cathode electrode.
[0082] Step 2: Preparation of carbon-wrapped wire mesh anode electrode
[0083] Soak a 5cm*5cm wire mesh in 0.5M HCl, 1M NaOH, and H2O for 2h. Place the wire mesh in a muffle furnace and heat treat it at 300℃ for 2h to obtain a pretreated wire mesh sample. Dissolve 0.2121g of o-phenanthroline and 0.66g of terephthalic acid in 50mL H2O, add 0.5mol / L of HNO3 dropwise, adjust the pH to 5, and obtain a ligand solution. Transfer the ligand solution to a hydrothermal reactor, control the filling amount to 80%, then place the wire mesh sample in the reactor, hydrothermally react at 120℃ for 24h, take out the wire mesh, rinse it, and place it in a muffle furnace. Use argon or nitrogen as a protective gas, heat it to 900℃ at a rate of 5℃ / min, keep it warm for 2h, and cool it to room temperature to obtain an anode electrode.
[0084] Step 3: System construction and operation
[0085] The prepared carbon-wrapped wire mesh was buried flat at 5 cm below the interface between the bottom mud and water to form an anode; the Ag-g-C3N4 / TiO2 / Ti surface of the prepared cathode electrode was facing upward and the activated carbon fiber felt surface was facing downward, the width of the interlayer polyethylene plastic foam was adjusted, and the cathode was horizontally suspended 2 cm below the water surface to form a cathode; the anode electrode and the cathode electrode were connected to the battery through a wire, and the system was successfully started.
[0086] Comparative Example 1
[0087] The preparation process of this comparative example 1 refers to that of Example 1, except that in step 1, carbon felt material is used as the cathode electrode material to construct the cathode electrode.
[0088] Comparative Example 2
[0089] The preparation process of this comparative example 2 refers to that of example 1, except that in step 3, the cathode and the anode are not connected by a wire and are in an open circuit state.
[0090] Comparative Example 3
[0091] The preparation process of this comparative example 3 refers to that of Example 1, except that in step 1, no photosynthetic algae is added to the cathode electrode.
[0092] Comparative Example 4
[0093] The preparation process of this comparative example 4 refers to that of Example 1, except that when preparing the cathode electrode material in step 1, the obtained sample is not treated in the mixed solution B, and the obtained electrode material is a TiO2 / Ti cathode electrode material.
[0094] Comparative Example 5
[0095] The preparation process of this comparative example 5 refers to that of Example 1, except that when preparing the cathode electrode material in step 1, no AgNO3 is added to the mixed solution B, and the obtained electrode material is g-C3N4 / TiO2 / Ti cathode electrode material.
[0096] After a period of operation, samples were collected regularly from the overlying water and sediment to determine the restoration efficiency of the water and sediment. The experimental results are as follows: Figure 3 , Figure 4 and Figure 5 shown.
[0097] The experiment of comparative example 1 shows that there are a large number of indigenous microorganisms in the sediment, which can spontaneously degrade the organic matter in the sediment. However, due to the limited cathode reaction, it is difficult to supply the large amount of electrons generated and the growth environment is poor, resulting in low performance in removing organic matter from the sediment. After 60 days of operation, the removal rate is only 3.8%. The experiment of comparative example 2 shows that when the photoelectrocatalysis is placed in the overlying water body, the removal rate of organic matter in the sediment is only 2.1%. It is confirmed that relying solely on microbial metabolism cannot achieve efficient removal of organic matter in the sediment. In Examples 1 and 2 of this scheme, the removal rates of organic matter in the sediment are as high as 28.7% and 25.9%, respectively, and the treatment efficiency is much higher than that of traditional microbial fuel cells and photocatalysis, indicating that the system couples the photoelectrocatalysis with the sedimentation-type microbial fuel cell, and can transfer the electrons generated by the anode of the sedimentation-type microbial fuel cell to the cathode, promote the metabolism of microorganisms, and enhance the performance of sediment repair. In addition, when photosynthetic algae were not added to the cathode electrode (such as comparative example 3), the organic matter removal rate in the sediment was 16.8%, indicating that the photosynthesis of algae produced oxygen, increased the oxygen content of the overlying water, promoted the photoelectrocatalytic production of more active groups, and improved the cathode reaction efficiency, thereby effectively improving the anode's organic pollutant treatment capacity.
[0098] The experimental results confirmed that after a period of operation, the water quality of the overlying water body was significantly improved. Figure 4As shown. The experimental results of comparative example 1 show that the cathode reduction reaction of the sedimentation-type microbial fuel cell has a weak effect on the removal of ammonia nitrogen from the overlying water body. After 60 days of operation, the removal rate is only 26.3%. The experimental results of comparative example 2 show that the active free radicals produced by photocatalysis have the function of removing ammonia nitrogen, but its performance is not high, and the removal rate is only 20.1%. In Examples 1 and 2 of the present invention, the ammonia nitrogen removal rate of the overlying water body is as high as 95.6% or more, and its treatment efficiency is much higher than that of traditional microbial fuel cells and photocatalysis. Similarly, when photosynthetic algae are not added to the cathode electrode (Comparative Example 3), the ammonia nitrogen removal rate of the overlying water body is only 78.8%, which proves that algae photosynthesis increases the oxygen content of the overlying water body and promotes the photoelectric catalysis to produce more active groups, thereby effectively improving the cathode photoelectric catalytic treatment capacity. In addition, Figure 5 The results are the experimental results of TOC removal in the overlying water. The results also further confirmed that this system couples photoelectrocatalysis with sedimentation-type microbial fuel cells, and can transfer the electrons generated by the anode of the sedimentation-type microbial fuel cell to the cathode, overcoming the shortcomings of the cathode photoelectrocatalytic material, such as easy recombination of photogenerated charges and low catalytic efficiency, and improving the degradation performance of overlying water pollutants. At the same time, the characteristics of biological algae photosynthesis and oxygen production can effectively promote the reaction efficiency of the cathode photoelectrode, generate more free radicals, and promote the purification speed of the overlying water.
[0099] in addition, Figure 6The above is a graph of the ammonia nitrogen removal rate of the overlying water body under the operating conditions of Example 1, Example 2, Comparative Example 1, Comparative Example 4 and Comparative Example 5. The experimental results of Comparative Example 1 show that when the carbon felt material without photocatalytic function is used as the cathode electrode material, the ammonia nitrogen in the overlying water body has a weaker removal effect, which should be attributed to the cathode reduction reaction of the microbial fuel cell. The results confirm that photoelectrocatalysis plays an important role in the coupling system. The experimental results of Comparative Example 4 show that when the TiO2 / Ti electrode material is used as the cathode electrode material, the ammonia nitrogen removal performance of the overlying water body is significantly improved, but the removal rate is only 28.5%. This is because the band gap of TiO2 is wide and the utilization efficiency of sunlight is limited. When the g-C3N4 / TiO2 / Ti electrode material is used as the cathode electrode material (Comparative Example 5), the ammonia nitrogen removal performance of the overlying water body is further enhanced, and the removal rate reaches 76.3%. This is because the composite of g-C3N4 and TiO2 can significantly improve its charge transfer and visible light absorption capacity, thereby improving its photoelectrocatalytic performance. In addition, it can be clearly found that with the extension of the operating time, the ammonia nitrogen removal performance of the overlying water body in Comparative Examples 4 and 5 shows a trend of first increasing and then decreasing. This is because a large number of microorganisms parasitize on the electrode surface, reducing its utilization efficiency of sunlight. In Examples 1 and 2 of this scheme, the ammonia nitrogen removal performance of the overlying water body is maintained at a high level, and there is no obvious downward trend. Therefore, the Ag-g-C3N4 / TiO2 / Ti cathode electrode material developed by the present invention has antibacterial properties, can effectively inhibit the growth of microorganisms on the surface of the cathode electrode, and maximizes the use of clean and cheap sunlight, ensuring its overlying water body repair performance and long-term operation stability.
[0100] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A self-sustaining method for in-situ remediation of shale gas flowback fluid, characterized in that: The steps include: Step 1: Preparation of Ag-g-C3N4 / TiO2 / Ti cathode electrode S1-1: Prepare solution: disperse hexadecyltrimethylammonium chloride and sodium hydroxide in water to obtain a mixed solution A; disperse silver nitrate and dicyandiamide in water to obtain a mixed solution B; S1-2: Preparation of cathode electrode material: firstly, the titanium mesh is placed in the mixed solution A for hydrothermal reaction, and after cooling, it is immersed in a hydrochloric acid solution and washed with deionized water; then, it is calcined, cooled, and immersed in the mixed solution B, and freeze-dried; finally, it is wrapped with tin foil and calcined to obtain Ag-g-C3N4 / TiO2 / Ti cathode electrode material; S1-3: Preparation of cathode electrode: placing activated carbon fiber felt and Ag-g-C3N4 / TiO2 / Ti cathode electrode material in parallel, surrounding the edges with polyethylene plastic foam to form an internal cavity, and filling the cavity with photosynthetic algae to obtain a cathode electrode; Step 2: Preparation of carbon-wrapped wire mesh anode electrode S2-1, pre-treatment of wire mesh; S2-2, preparing a ligand solution: dispersing o-phenanthroline and terephthalic acid in water, adjusting the pH, and obtaining a ligand solution; S2-3, preparing the anode electrode: subjecting the pretreated wire mesh sample to a hydrothermal reaction in the ligand solution, taking out the wire mesh, rinsing it, and then calcining it under a protective gas, and cooling it to obtain the anode electrode; Step 3: System construction and operation S3-1. Installation system: In a waste liquid system to be treated having a bottom mud layer and a water layer after standing, the above-mentioned anode electrode is installed in the bottom mud layer, and the cathode electrode is installed in the water layer. When the cathode electrode is installed, one side of the Ag-g-C3N4 / TiO2 / Ti electrode faces upward, and one side of the activated carbon fiber felt faces downward; S3-2. System operation: The anode electrode and the cathode electrode are connected to each other through a wire and connected to a battery; samples are collected from the overlying water and bottom sediment regularly to determine the restoration efficiency of the water body and bottom sediment.
2. A method for in-situ remediation of self-sustaining shale gas flowback fluid according to claim 1, characterized in that: In S1-1, the mass ratio of hexadecyltrimethylammonium chloride, sodium hydroxide and water in the mixed solution A is 16-64:240:1000; the mass ratio of dicyandiamide, silver nitrate and water in the mixed solution B is 16.81-37.62 g:0.1699-0.8494:
100.
3. A method for in-situ remediation of self-sustaining shale gas flowback fluid according to claim 1, characterized in that: In S1-2, the hydrothermal reaction is carried out at 140-160°C for 24 hours; the immersion in the hydrochloric acid solution is carried out in a 1-2M hydrochloric acid solution for 24 hours; and the calcination is carried out by heating the temperature to 500-550°C at a rate of 2-4°C / min and keeping the temperature for 2.5-4 hours.
4. A self-sustaining in-situ remediation method for shale gas flowback fluid according to claim 1, characterized in that: In S1-2, the immersion time in the mixed solution B is 24 to 36 hours; and the calcination is performed at 520 to 540° C. for 4 hours.
5. The method for in-situ remediation of self-sustaining shale gas flowback fluid according to claim 1, characterized in that: In S1-3, the distance between the activated carbon fiber felt and the Ag-g-C3N4 / TiO2 / Ti cathode electrode was 2 to 3 cm.
6. A self-sustaining in-situ remediation method for shale gas flowback fluid according to claim 1, characterized in that: In S2-1, the pretreatment of the wire mesh includes immersing the wire mesh in 0.5M hydrochloric acid solution, 1M sodium hydroxide solution and water for 2 hours in sequence; then placing the wire mesh in a muffle furnace and heat treating it at 300-350°C for 2 hours to obtain a pretreated wire mesh sample.
7. A self-sustaining in-situ remediation method for shale gas flowback fluid according to claim 1, characterized in that: In S2-2, the mass ratio of o-phenanthroline, terephthalic acid and water in the ligand solution is 0.18-0.36:0.66:
50.
8. The method for in-situ remediation of self-sustaining shale gas flowback fluid according to claim 1, characterized in that: In S2-3, the hydrothermal reaction is carried out at 120-140°C for 24-48h. The wire mesh is taken out, rinsed clean, and placed in a muffle furnace. Argon or nitrogen is used as a protective gas, and the temperature is increased to 850-900°C at a rate of 3-5°C / min. The temperature is kept for 2-3h and the anode electrode material is obtained after cooling to room temperature.
9. An Ag-g-C3N4 / TiO2 / Ti cathode electrode material, prepared by the method described in any one of claims 1 to 5.
10. A self-sustaining shale gas flowback fluid in-situ remediation system, characterized by: The invention comprises a waste liquid system to be treated which has a bottom mud layer and a water layer after standing, wherein a cathode electrode is arranged in the water layer, an anode electrode is arranged in the bottom mud layer, and the anode electrode is 2 to 10 cm away from the contact interface between the water layer and the bottom mud layer; the anode electrode is a carbon-wrapped wire mesh prepared by the method according to any one of claims 1 to 8; the cathode electrode is an Ag-g-C3N4 / TiO2 / Ti cathode electrode prepared by the method according to any one of claims 1 to 8; When the cathode electrode is installed, one side of the Ag-g-C3N4 / TiO2 / Ti cathode electrode material faces upward, the other side of the activated carbon fiber felt faces downward, and the cathode electrode is horizontally suspended 2 to 10 cm below the water surface; the anode electrode and the cathode electrode are connected to each other through a wire and connected to a battery for collecting electrical energy.
Citation Information
Patent Citations
Method for improving photocathode performance through semiconductor metal semiconductor multilayer heterostructure
CN116265615A
Method for manufacturing high discharge-resistant and high stability carbon nanotube field emission electron beam emitter using metal binders and carbon nanotube field emission electron beam emitter manufactured by the method
WO2013154361A1